Syntactic development and verbal short-term memory of children with autism spectrum disorders having intellectual disabilities and children with down syndrome. (June 2022) - Koizumi, Manami; Kojima, Michio
Background and aims: Previous studies suggest that syntactic development in children with intellectual disabilities (ID) is positively correlated with verbal short-term memory (VSTM). This study investigated the characteristics of syntactic development and their relationships of VSTM in children with ID based on type. Methods: The participants were children with ID ( N  = 34), including 14 children with autism spectrum disorders (ASD), 20 with Down syndrome (DS), with chronological ages from 8 years 10 months to 18 years 4 months and nonverbal mental ages (MA) of over 4 years, and typically developing (TD) children ( N  = 21) with chronological ages from 5 years 0 months to 5 years 10 months. They were assessed using VSTM, syntactic comprehension, and expression tasks. Results: The results showed that both the ASD and DS groups performed significantly lower on the syntactic comprehension task and the syntactic expression task than the TD group with the same nonverbal MA in the complex aspect of grammatical structure. In the VSTM task, the ASD group showed significantly lower performance in sentence and story repetition tasks than the TD group of the same nonverbal MA. The DS group showed significantly lower performance in forward digit span, and word, nonword, sentence, and story repetition tasks than the TD group of the same nonverbal MA. Conclusions: These results suggest that children with ASD have difficulty in understanding and remembering linguistic information with complex semantic structures, and children with DS have a small capacity for VSTM, affecting their syntactic development.